My mind is a mountain = Mi mente es una montaña - Montenegro, Cindy (Little Libros, LLC, 2022)
"A little boy goes on a journey to discover a full range of emotions, from feelings of great enthusiasm and happiness to those of sorrow and anger. My mind is a mountain if a metaphor for the heights a mind can reach in powerfully handling all emotions from the lowest of the lows to the highest of the highs -- and everything in between."--Page [2] of cover.